KONSEP PENDIDIKAN TASAWUF PADA REMAJA MILENIAL - Amar Habibi; Suklani (CV. ADIBA ASIHA AMIRA, 2023)
Tasawuf education serves to make humans have pious personalities, good and noble behavior, and the best worship, producing the output in the form of honest, istiqāmah and tawadu humans. Tasawuf education for teenagers is really needed to prevent juvenile delinquency. This article aimed to identify and understand the concept of tasawuf education in order to prevent juvenile delinquency. This article used a literature review approach. The literature search was conducted online through Google Scholar which was limited from 2012-2022 with the search process using the keywords of